Gridded daily rainfall data for Ghana for the period 1960 - 2015: Approach and validation process - Steve Ampofo; Thompson Annor; Jeffrey N.A. Aryee; Jacob Agyekum; Leonard K. Amekudzi (Data in Brief, 2023)
Rainfall data is necessary at resolutions that allow modelling of environmental change and its impact on socio-economic well-being. This is particularly so with agricultural output determination in much of Africa with Ghana not exemption, where data is required for intra and inter-seasonal assessment of the impact of rainfall on yield. However, the sparse and limited distribution data from gauge measurements, coupled with periods of no record of daily rainfall data, limit their application for any meaningful endeavour. This data cures such deficiency by generating a high resolution (0.25° × 0.25°) gridded daily rainfall using the Minimum Surface Curvature (MSC) interpolation for 190 stations distributed across all agro-climatic zones of Ghana. Validation is done using 19 Ghana Meteorological Agency (GMet) gauge stations (10%) by comparing the; ratios, correlations and Root Mean Square Error (RMSE) of the observed to the gridded for the seasons.